Autophagy initiation correlates with the autophagic flux in 3D models of mesothelioma and with patient outcome. Issue 7 (2nd July 2016) - Follo, Carlo; Barbone, Dario; Richards, William G.; Bueno, Raphael; Broaddus, V. Courtney
ABSTRACT: Understanding the role of autophagy in cancer has been limited by the inability to measure this dynamic process in formalin-fixed tissue. We considered that 3-dimensional models including ex vivo tumor, such as we have developed for studying mesothelioma, would provide valuable insights. Using these models, in which we could use lysosomal inhibitors to measure the autophagic flux, we sought a marker of autophagy that would be valid in formalin-fixed tumor and be used to assess the role of autophagy in patient outcome. Autophagy was studied in mesothelioma cell lines, as 2-dimensional (2D) monolayers and 3-dimensional (3D) multicellular spheroids (MCS), and in tumor from 25 chemonaive patients, both as ex vivo 3D tumor fragment spheroids (TFS) and as formalin-fixed tissue. Autophagy was evaluated as autophagic flux by detection of the accumulation of LC3 after lysosomal inhibition and as autophagy initiation by detection of ATG13 puncta. We found that autophagic flux in 3D, but not in 2D, correlated with ATG13 positivity. In each TFS, ATG13 positivity was similar to that of the original tumor. When tested in tissue microarrays of 109 chemonaive patients, higher ATG13 positivity correlated with better prognosis and provided information independent of known prognostic factors. Our results show that ATG13 is a static marker of the autophagic flux in 3D models of mesothelioma and may also reflect autophagy levels in formalin-fixed tumor. If confirmed, this marker would represent a novel prognostic factor for mesothelioma, supporting the notion that autophagy plays an important role in this cancer.